Cytotoxic Effects of Recombinant StxA2-His in the Absence of Its Corresponding B-Subunit - Laura Heinisch; Maike Krause; Astrid Roth; Holger Barth; Herbert Schmidt (Toxins, 2021)
AB5 protein toxins are produced by certain bacterial pathogens and are composed of an enzymatically active A-subunit and a B-subunit pentamer, the latter being responsible for cell receptor recognition, cellular uptake, and transport of the A-subunit into the cytosol of eukaryotic target cells. Two members of the AB5 toxin family were described in Shiga toxin-producing Escherichia coli (STEC), namely Shiga toxin (Stx) and subtilase cytotoxin (SubAB). The functional paradigm of AB toxins includes the B-subunit being mandatory for the uptake of the toxin into its target cells. Recent studies have shown that this paradigm cannot be maintained for SubAB, since SubA alone was demonstrated to intoxicate human epithelial cells in vitro. In the current study, we raised the hypothesis that this may also be true for the A-subunit of the most clinically relevant Stx-variant, Stx2a. After separate expression and purification, the recombinant Stx2a subunits StxA2a-His and StxB2a-His were applied either alone or in combination in a 1:5 molar ratio to Vero B4, HeLa, and HCT-116 cells. For all cell lines, a cytotoxic effect of StxA2a-His alone was detected. Competition experiments with Stx and SubAB subunits in combination revealed that the intoxication of StxA2a-His was reduced by addition of SubB1-His. This study showed that the enzymatic subunit StxA2a alone was active on different cells and might therefore play a yet unknown role in STEC disease development.